PENGARUH SISTEM INFORMASI AKUNTANSI PENJUALAN DAN SISTEM AKUNTANSI PENERIMAAN KAS: : TERHADAP EFEKTIVITAS PENGENDALIAN PIUTANG PADA PT. ABSOLUTE CONNECTION - Wulandari, Rika; Suryaningsih, Maria (Jurnal Akuntansi, 2024)
This study examines the impact of sales accounting information systems and cash receipt accounting systems on the effectiveness of accounts receivable control at PT Absolute Connection. Using a quantitative approach, data was collected from 63 respondents via a saturated sampling method and analyzed using SPSS version 26. The results indicate that both the sales accounting information system and the cash receipt accounting system have a significant effect on the effectiveness of controlling receivables, both partially and simultaneously. Consequently, the study suggests that the company should continuously develop its sales information systems and tailor its cash receipt processes to operational needs to further enhance receivable management efficiency.